Linguistik als Kampfsport – Ein Plädoyer für die Suche nach Paradigmen demokratischen Sprechens in Alltag, Medien und Recht - Vogel, Friedemann (Linguistik Online, 2014)
Following Bourdieu's notion of applied research this contribution asks for the possibility of linguistics as a kind of "martial art" and "self-defence", i. e. linguistics trying to interfere in society based on a holistic model of human rights and paradigms of democratic speech. In this perspective the text discusses elements of a normative model, which is able to lead linguistic research practices and explores the context of education, law and the media formation of par-ticipation. Finally I will consider the meaning of speech practices and linguistic research or methods in the context of capitalism and profit.